THEORETICAL RESEARCH ON CUTTING METHODS USED IN THE AUTOMOTIVE INDUSTRY - Alexandru Vasile Oancea; Corneliu Rontescu; Ana Maria Bogatu; Dumitru Titi Cicic; Catalin Gheorghe Amza (Nonconventional Technologies Review)
The present paper presents modern methods of cutting metallic materials used in the automotive industry, highlighting essential theoretical principles, process efficiency, cut quality, and economic implications. Among the methods discussed are laser cutting, water jet cutting, and electrical discharge machining (EDM), each having specific characteristics that determine their applicability in various industrial fields. A review of the specialized literature shows that laser cutting and water jet cutting offer significantly higher cutting speeds and superior precision compared to traditional methods, making them preferred solutions in high-demand production environments. In contrast, mechanical cutting, although slower, proves to be a viable option for workshops with limited budgets or for the production of unique or small series parts.The paper analyzes cutting methods in terms of operational costs, cutting precision, cutting speed, and equipment costs, highlighting that selecting the optimal cutting method is a matter of cost, efficiency, and the long-term vision of the management of the user company.